A novel nomogram based on prognostic factors for predicting venous thrombosis risk in lymphoma patients. Issue 10 (24th August 2021) - Yang, Jingshi; Zhang, Yuqin; Yang, Peipei; Zhang, Xiaolu; Li, Mei; Zou, Liqun
Abstract: Lymphoma-associated venous thromboembolism (VTE) can be a serious complication in lymphoma patients. We designed a nomogram as a guide to estimate the VTE risk in lymphoma patients. We retrospectively analyzed 555 Chinese lymphoma patients who were newly diagnosed at West China Hospital. The nomogram was generated based on multivariate regression coefficients. The multivariate analysis indicated that advanced clinical stage ( p  < .001*), Hodgkin lymphoma ( p  = .045*), and prechemotherapy Hb level <115 g/L ( p  = .01*) were independent risk factors for VTE in lymphoma patients. A calibration plot and the area under the receiver operating characteristic curve were used to validate the novel nomogram. The nomogram displayed a good C-index (0.73), and the calibration plot showed excellent agreement between the predicted and actual probabilities. The AUROC of the nomogram was 0.731, demonstrating a strong discriminatory ability. Notably, the predictive value of the nomogram was better than the Khorana risk score.